Radio Spectrum Management: Policies, Regulations and Techniques - Mazar (Madjar), Haim (Wiley, 2016)
This book presents the fundamentals of wireless communications and services, explaining in detail what RF spectrum management is, why it is important, which are the authorities regulating the use of spectrum, and how is it managed and enforced at the international, regional and national levels. The book offers insights to the engineering, regulatory, economic, legal, management policy-making aspects involved. Real-world case studies are presented to depict the various approaches in different countries, and valuable lessons are drawn. The topics are addressed by engineers, advocates and economists employed by national and international spectrum regulators. The book is a tool that will allow the international regional and national regulators to better manage the RF spectrum, and will help operators and suppliers of wireless communications to better understand their regulators.